An Aboriginal Economy: Nguiu, Northern Territory - Stanley, Owen (Australian National University. North Australia Research Unit, 1983)
Conclusion: The simultaneous achievement of the goals of reducing dependence on aid and increasing per capita income will be difficult. In terms of general strategies, if Nguiu is to achieve these things it will have to develop activities which will yield substantial long-term profits. Like the Northern Territory generally, the best prospects for the moment lie in the areas of tourism and mining, if minerals are found. Other industries may have an important role in providing incomes and employment but they are unlikely to provide the substantial funds required for development in the long run